2001
DOI: 10.1021/ie010272q
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkali Metal Oxide Additives on Cu/SiO2 Catalyst in the Dehydrogenation of Ethanol

Abstract: A series of Cu/SiO2 catalysts with various alkali metal oxide additives was investigated to elucidate the effects of additives on the catalytic properties of copper catalysts in the dehydrogenation of ethanol. The catalysts were prepared by the impregnation method and were characterized by X-ray diffraction, temperature-programmed reduction, temperature-programmed desorption of CO2, and H2−N2O titration. The dehydrogenation reaction was carried out in a continuous-flow reactor at 300 °C under atmospheric press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…[5,6] Monometallic Cu-based catalysts are widely used for this reaction; however, quick deactivation of copper takes place, attributed to copper particle sintering. [4,7]. On the other hand, the oxidative dehydrogenation (ODH) of ethanol to acetaldehyde and water is the oldest laboratory method to produce acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5,6] Monometallic Cu-based catalysts are widely used for this reaction; however, quick deactivation of copper takes place, attributed to copper particle sintering. [4,7]. On the other hand, the oxidative dehydrogenation (ODH) of ethanol to acetaldehyde and water is the oldest laboratory method to produce acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] On the other hand, as mentioned above, the catalytic activity of Cu has been found to decrease rapidly even in the first hour of the reaction, where the deactivation has been attributed to the sintering of metallic Cu at the high dehydrogenation temperature. [7,14] In searching for a promoter to inhibit the sintering of Cu, it has been reported that the incorporation of chromium oxide into Cu improves the catalyst stability. [13,15,16] However, the adverse environmental issues associated with the use of chromium have discouraged the application of this approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,11] Reducing the density of Si-OH over SiO 2 surface is an effective way of promoting selectivity, but simultaneously leading to instability. [12] Compared with SiO 2 , carbon materials possess relatively inert surface. [13] The Cu/C catalyst shows a substantially improved acetaldehyde selectivity by minimizing the secondary reactions.…”
Section: Introductionmentioning
confidence: 99%